DDIT3 overexpression increases odontoblastic potential of human dental pulp cells. (16th April 2014) - Wu, Y.; Sun, H.; Song, F.; Fu, D.; Wang, J.
Abstract Objectives Human dental pulp cells (HDPCs) with multi‐potential differentiational capacity can undergo odontoblastic differentiation when stimulated with proinflammatory cytokines. However, factors linking proinflammatory stimuli and their odontoblastic differentiation have, as yet, not been completely understood. As an apoptotic transcription factor, DDIT3 plays a crucial role in the inflammatory reaction and in osteogenic differentiation. Thus, we hypothesized that DDIT3 may participate in odontoblastic differentiation of HDPCs. Materials and methods Immunofluorescent staining was used to detect expression of DDIT3 in HDPCs and effects of TNFα, on its nuclear accumulation. HDPCs that overexpressed DDIT3 were developed and their proliferation and odontoblastic differentiation abilities were examined. qRT‐PCR was employed to detect mineralization‐related genes, including ALP, runt‐related transcription factor‐2 (Runx2), osterix (OSX), dentin sialophosphoprotein (DSPP), dentin matrix acidic phosphoprotein 1 (DMP1) and osteocalcin (OCN). Western blot analysis was performed to detect expression of DSPP protein. Results DDIT3 was expressed in HDPCs. TNFα treatment enhanced mRNA expression as well as nuclear accumulation of DDIT3 (slightly). DDIT3 overexpression reduced HDPC proliferation, however, it increased their calcium nodule formation and expression of OSX, DSPP, DMP1 and OCN. Conclusions DDIT3 may be a factor that links proinflammatory stimuli and differentiation of HDPCs.